Evaluating music performance and context-sensitivity with Immersive Virtual Environments - Donald Glowinski; Naëm Baron; Kanika Shirole (EAI Endorsed Transactions on Creative Technologies, 2015)
This study explores a unique experimental protocol that evaluates how a musician’s sensitivity to social context during performance can be analysed through a combination of behavioral analysis, self-report and Immersive Virtual Environment (IVE). An original application has been developed to create audience of avatars that display different motivational states that are known to affect musician's performance. The musicians’ body expressions have then been recorded through a motion capture system and analysed as they relate to audience motivational state. The musician subjective experience has been captured after each performance through semi-structured interviews. Preliminary results depict the strategies implicitly employed by four expert violinists during their performances under the various contexts (empty room and engaged and disengaged audience of avatars). Finally, this study discusses the way to improve methodology, analyses and real-world responses to musician's needs.